2021
DOI: 10.1016/j.actamat.2021.117433
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the efficacy of concentrated interstitial carbon in enhancing the pitting corrosion resistance of stainless steel

Abstract: By introducing a high fraction of interstitial carbon through low temperature carburization, the pitting corrosion resistance of austenitic stainless steel can be signi cantly improved. Previous work attributed this enhancement to the improvement of passive lm properties. However, we show here that interstitial carbon actually weakens the passive lm on stainless steel. In fact, the enhancement in pitting resistance is a result of carbon reducing the metal dissolution rate in a local pit environment by many ord… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(9 citation statements)
references
References 64 publications
(34 reference statements)
0
3
0
Order By: Relevance
“…[ 34 ] Li et al reported that the bonds between interstitial carbon and metal atoms in stainless steels were 1.4–2.0 times stronger than the metal–metal bonds. [ 35 ] Note that in this study, it was impossible to measure the interstitial‐carbon concentration within each phase. However, it seemed reasonable to assume that the increase in the pitting corrosion resistance could be attributed to the reduction in the metal dissolution rate resulting from the interstitial carbon in the local environment of the pits and that interstitial carbon inhibited the transition from metastable pitting to stable pit growth.…”
Section: Resultsmentioning
confidence: 99%
“…[ 34 ] Li et al reported that the bonds between interstitial carbon and metal atoms in stainless steels were 1.4–2.0 times stronger than the metal–metal bonds. [ 35 ] Note that in this study, it was impossible to measure the interstitial‐carbon concentration within each phase. However, it seemed reasonable to assume that the increase in the pitting corrosion resistance could be attributed to the reduction in the metal dissolution rate resulting from the interstitial carbon in the local environment of the pits and that interstitial carbon inhibited the transition from metastable pitting to stable pit growth.…”
Section: Resultsmentioning
confidence: 99%
“…In our previous work, we have shown that by calculating DFT energies for a series of supercells with changing compositions and counting the bonds between the different species in them, the different cohesive energies can be well fitted. [ 41,51 ] We have also shown that in more polar or ionic structures where charge transfer significantly affects the bond strength and the bond energy between two elements changes when other elements are present, the introduction of a bond synergy parameter can appropriately modify the bond strength as a function of composition, [ 52 ] which we, however, found to not be necessary here.…”
Section: Resultsmentioning
confidence: 99%
“…For example, carbon is known to decrease the corrosion resistance of stainless steels; however, recent studies reveal that interstitial carbon contributes to the improvement of dissolution resistance of stainless steels and inhibits pitting corrosion. [63][64][65][66] The pitting corrosion resistance of stainless steels varies with inclusion composition, and alloy design for modifying the inclusions has been found to be effective in the prevention of pitting. To conclude, a systematic investigation of the relationship between the electrochemical properties of microstructural features and the pitting corrosion resistance of stainless steels is essential to transform the experience-based knowledge into a well-established technology.…”
Section: Discussionmentioning
confidence: 99%